Highly sensitive force sensor based on balloon-like interferometer. (July 2018) - Wu, Yue; Xiao, Shiying; Xu, Yao; Shen, Ya; Jiang, Youchao; Jin, Wenxing; Yang, Yuguang; Jian, Shuisheng
Highlights: Balloon-like interferometer for force measurement has been presented. The fiber sensor has advantage of easy fabrication and low cost. The relationship between bending diameter and force is investigated. The proposed fiber sensor has the force sensitivity of 24.9 pm/μN. Abstract: An all-fiber highly sensitive force sensor based on modal interferometer has been presented and demonstrated. The single-mode fiber (SMF) with coating stripped is designed into a balloon-like shape to form a modal interferometer. Due to the bent SMF, the interference occurs between the core mode and cladding modes. With variation of the force applied to the balloon-like interferometer, the bending diameter changes, which caused the wavelength shift of the modal interference. Thus the measurement of the force variation can be achieved by monitoring the wavelength shift. The performances of the interferometer with different bending diameter are experimentally investigated, and the maximum force sensitivity of 24.9 pm/ μ N can be achieved with the bending diameter 14 mm ranging from 0 μ N to 1464.12 μ N. Furthermore, the proposed fiber sensor exhibits the advantages of easy fabrication and low cost, making it a suitable candidate in the optical fiber sensing field.